The Isotopic Composition of Sulphur in Meteorites and Sea Water Sulphates - Warren, John (1954)
The isotopic composition of meteorite sulphur and sea water sulphates was investigated by means of a simultaneous collection mass spectrometer. It was found that sixteen samples of meteorite sulphur possessed identical isotope abundances within the precision of the instrument. The sulphates from various depths in the Atlantic, Pacific and Arctic Oceans, were found to be enriched in s34 compared to the meteorite base level. The overall variation in s32/s34 content was 0.39 percent for the sea water samples. Thesis Master of Science (MS)